Third-Party Testing Nutritional Supplement Knowledge, Attitudes, and Use Among an NCAA I Collegiate Student-Athlete Population - Vento, Kaila Ann; Wardenaar, Floris Cornelis (Frontiers in Sports and Active Living, 2020)
Dietary supplements, sports foods, and ergogenic supplements are consumed to increase performance, recovery, and health, but risk contamination with illegal substances. Third-party testing programs may assist in regulating the purity and safety of supplements, yet athletes’ attitudes and use of such programs are not widely reported. This study examined nutritional supplement knowledge, attitudes, and use, as well as the purchase of third-party tested supplements among university student-athletes (N= 138). Knowledge of nutritional supplements yielded a median and (IQR) score of 25% (17 to 42%). Sixteen percent of student-athletes said they were knowledgeable about supplements and their effects, p< 0.001. All athletes stated they used a dietary supplement or sports food at least once within the last 12 months, and 77% consumed at least one ‘claimed to be’ ergogenic supplement. Sixty-six percent of student-athletes purchased nutritional supplements not provided by the athletic department. Females athletes were more likely to consume a combination of vitamins and single minerals, a larger variety of sports foods, exotic berries, herbs, maca root powder, ribose, ephedra, colostrum, and hydroxy-methyl-buterate (HMB) than males. Over 90% believed it was essential to know if a supplement was third-party tested. However, only 57% stated the supplements bought were third-party tested. No sex differences were found for nutritional supplement knowledge, attitudes, and use of third-party testing programs. Our results indicate a need to improve student-athletes’ attitudes toward and knowledge of nutritional supplements, and the initiation of programs to assist in the choosing and consuming of third-party tested supplements.